Experience in complex etiopathogenetic therapy of rotavirus infection in children: the effectiveness of innovation - S. G. Gorbunov; L. N. Mazankovа; E. A. Degtyareva; L. A. Minayeva; A. N. Oskin (Детские инфекции (Москва))
The article presents the clinical effectiveness of complex etiopathogenic therapy of rotavirus infection in children using a combination of «Adiarin» — tannate gelatin, hyposmolar rehydration solution and probiotic containing lactobacilli LGG and bifidobacteria BB-12. It was found that in patients receiving innovative treatment, compared with children who were on traditional therapy, fever was significantly less frequent, its duration and hospitalization time were reduced by 2.4 days. In addition, acidosis was significantly less pronounced in this group compared to the control group. Thus, the use of the «Adiarin» line of products contributes to a faster recovery of children with rotavirus infection compared to patients who received standard treatment.